1974
DOI: 10.1111/j.1471-4159.1974.tb06913.x
|View full text |Cite
|
Sign up to set email alerts
|

THE SUBSYNAPTOSOMAL LOCALIZATION OF HISTAMINE HISTIDINE DECARBOXYLASE AND HISTAMINE METHYLTRANSFERASE IN RAT HYPOTHALAMUS1

Abstract: Abstract— We have examined the subcellular localization of histamine, histamine methyltransferase (EC 2.1.1.8) (HMT) and histidine decarboxylase (EC 4.1.1.22) in rat hypothalamus after osmotic lysis of synaptosome‐containing primary particulate fractions. When crude mitochondrial fractions are subjected to osmotic lysis, histamine is retained within particulate structures, while HMT is released into the supernatant fluid. The majority of histidine decarboxylase activity is also recovered in the supernatant flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Perfusion of the cerebral ventricles of the cat with labeled histamine or labeled histidine revealed that the yield of labeled methylhistamine, relative to labeled histamine, was much higher from labeled histamine than from labeled histidine, fostering the suggestion the "endogenous brain histamine has a fate different from histamine introduced into the brain" (White, 1960). In brain, endogenous histamine is found in particulate fractions (Carlini and Green, 1963;see Hough and Green, 1984) while histamine methyltransferase is found in the cytosol (Brown et al, 1959;Snyder et al, 1974). In rat brain slices, the spontaneous effiux of exogenous histamine was six-fold higher than that of endogenous histamine, and the release of exogenous histamine was not influenced by conditions that modulated the release of endogenous histamine (Arrang et al, 1985).…”
Section: Endogenous and Exogenous Histaminementioning
confidence: 95%
“…Perfusion of the cerebral ventricles of the cat with labeled histamine or labeled histidine revealed that the yield of labeled methylhistamine, relative to labeled histamine, was much higher from labeled histamine than from labeled histidine, fostering the suggestion the "endogenous brain histamine has a fate different from histamine introduced into the brain" (White, 1960). In brain, endogenous histamine is found in particulate fractions (Carlini and Green, 1963;see Hough and Green, 1984) while histamine methyltransferase is found in the cytosol (Brown et al, 1959;Snyder et al, 1974). In rat brain slices, the spontaneous effiux of exogenous histamine was six-fold higher than that of endogenous histamine, and the release of exogenous histamine was not influenced by conditions that modulated the release of endogenous histamine (Arrang et al, 1985).…”
Section: Endogenous and Exogenous Histaminementioning
confidence: 95%
“…However, the intracellular localization of HDC remains to be clarified. In addition to the soluble form of HDC, membrane-associated HDC activity has been reported in various tissues, such as rat hypothalamus (24) and rat brain (25)(26)(27)(28). However, these reports did not refer to the molecular size of the membranous HDC.…”
mentioning
confidence: 99%
“…On subcellular fractionation, a portion, 15-40%, of histamine in rat and guinea pig brain is fo und in the P-l fraction, which has few synaptosomes (Carlini & Green 1963, Michaelson & Coffman 1967, Kataoka & DeRobertis 1967, Kuhar et al 1971, Young et al 1971, Snyder et al 1974, Dismukes et a1 1974, Martres et a1 1975, Barbin et a1 1976, Picatoste et al 1977, Schwartz et al 1979a. On subcellular fractionation, a portion, 15-40%, of histamine in rat and guinea pig brain is fo und in the P-l fraction, which has few synaptosomes (Carlini & Green 1963, Michaelson & Coffman 1967, Kataoka & DeRobertis 1967, Kuhar et al 1971, Young et al 1971, Snyder et al 1974, Dismukes et a1 1974, Martres et a1 1975, Barbin et a1 1976, Picatoste et al 1977, Schwartz et al 1979a.…”
mentioning
confidence: 99%